2010
DOI: 10.3390/molecules15042246
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Activity of New 4-Heteroarylamino Coumarin Derivatives Containing Nitrogen and Sulfur as Heteroatoms

Abstract: ynthesis, spectral analysis and bioactivity of new coumarin derivatives are described in this paper. Eight new coumarin derivatives were synthesized in moderate to good yields by condensation of 4-chloro-3-nitrocoumarin and the corresponding heteroarylamine. The synthesized compounds were tested for their in vitro antimicrobial activity, in a standard disk diffusion assay, against thirteen strains of bacteria and three fungal strains. They have shown a wide range of activity - from one completely inactive comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 21 publications
0
23
1
Order By: Relevance
“…In a previous study, compounds containing a thiophene ring were found to be more active than those containing furan or pyrrole rings 20. Many sulfur-containing compounds have been reported to have antimicrobial activity against bacteria 23,24. Similarities in the inhibition pattern could be noted between each of the following groups of compounds: 1A and 2A; 1B and 2B; 3B and 4B; and 3A, 4A, and 5A.…”
Section: Discussionmentioning
confidence: 78%
“…In a previous study, compounds containing a thiophene ring were found to be more active than those containing furan or pyrrole rings 20. Many sulfur-containing compounds have been reported to have antimicrobial activity against bacteria 23,24. Similarities in the inhibition pattern could be noted between each of the following groups of compounds: 1A and 2A; 1B and 2B; 3B and 4B; and 3A, 4A, and 5A.…”
Section: Discussionmentioning
confidence: 78%
“…Based on this we could conclude that a significant role in the onset of antimicrobial activity of these compounds play the heteroatoms in the heteroaryl ring substituent bounded to the coumarin framework. In support of this goes the fact that the activity of these compounds was significantly reduced or even completely lost in the case of sterically-hindered heteroatoms (Dekić et al, 2010b).…”
Section: Pharmacologymentioning
confidence: 73%
“…Nitration of 4-hydroxycoumarin 1 with a mixture of glacial acetic acid and concentrated nitric acid afforded 3-nitro-4-hydroxycoumarin 107 (Brady et al, 2004;Butler and Brown, 2002;Dekic et al, 2010;Ga et al, 2010;Park et al, 2007;Zhi-Qiang et al, 2014). Also, this nitration reaction was reported by Lei et al (2004) On the other hand, use of CAN on montmorillonite K-10 clay under microwave irradation for expeditious solvent-free regioselective nitration nitration of 4-hydroxycoumarin 1 has been revealed for the first time by Ganguly et al (2003) Scheme 57.…”
Section: Nitration Reactionmentioning
confidence: 99%